Risk Management Strategies in the Face of Global Market Uncertainty - Karsim Karsim; Deni Gunawan; Cindy Puspitafuri; Ahmad Junaidi (PT. Anagata Sembagi Education, 2024)
In today's dynamic global economy, organizations face increasing challenges in managing risk amidst market uncertainty. This paper addresses a gap in current research by focusing on innovative risk management strategies designed to effectively address these uncertainties. Using a qualitative research approach, this study investigates how organizations identify, assess, and mitigate risk through in-depth interviews and thematic analysis. The novelty lies in exploring the integration of traditional risk management frameworks with emerging qualitative methodologies to improve decision making and resilience. By leveraging qualitative insights, this research aims to uncover various risk factors that are often overlooked by quantitative approaches, thereby offering a comprehensive understanding of risk dynamics in complex global markets. This study contributes to advancing theoretical frameworks and practical applications in risk management, empowering organizations to proactively adapt and thrive in turbulent environments. Based on the evaluation that has been carried out, it can be stated that risk management plays a crucial role in influencing company performance. Risk management not only functions to manage company resources with efficiency, but also to optimize the results obtained so that the company can achieve the financial goals that have been set.